A Scalable QoS Scheduling Architecture For WiMAX Multi-Hop Relay Networks. - Tat, Chee Wan; Bayan, Anas F. (2010)
WiMAX Mobile Multi-hop Relay (MMR) network has been introduced to increase the capacity and extend the coverage area of a single WiMAX Base Station (BS) by the use of a Relay Station (RS).